(untitled) (Research, Society and Development, 2022)
Objective: To map the scientific evidence about the use of spatial analysis techniques to control the health status of the community at risk for arboviruses. Method: Scope review protocol, registered in the Open Science Framework, based on the Joanna Briggs Institute methodological trail and the Preferred Reporting Items for Systematic reviews and Meta checklist -Analyses extension for Scoping Reviews, the research will take place in the following databases: PubMed, Web Of Science and Scopus, will be guided by the following research question: “What is the evidence of the use of the spatial analysis tool as a nursing management strategy in public health for the assessment of Chikungunya, Dengue and Zika in the population with a view to controlling the health status of the community?”, the Rayyan software will be used to manage the collection and selection of published studies. Subsequently, the title and abstract of all identified studies will be evaluated, based on the established inclusion and exclusion criteria, by two independent reviewers and by a third reviewer to resolve possible discrepancies. Results will be descriptively summarized, a flowchart and narrative summary will accompany the results and describe how they relate to the objective and issue of the review. The information from the review instrumented from this protocol will be useful to categorize, differentiate and exemplify the correct use of spatial analysis techniques in studies with infectious diseases, providing knowledge to nurses, so that they can plan interventions and develop health actions of the community.